Distribution Optimization With The Transportation Method - Risna Kartika; Nuryanti Taufik; Marlina Nur Lestari (Universitas Muhammadiyah Jember, 2021)
Indonesia has several potential plantation commodities, one of them is tea plant, because tea is one of the most consumed beverages in the world. West Java Province accounts for 70% of national tea production. The X Indah Tea Factory is one of the managers of tea from the results of the people's tea plantations located in Tasikmalaya, which supplies processed dried tea to various cities. The tendency of high distribution costs requires a combination of the right product allocation so that it can make distribution costs to be optimal (minimum cost). The transportation method is a method used to find the cheapest way to distribute products from several sources (distribution centers: factories, warehouses) to several destinations so that total transportation costs are minimized. The transportation method used is North West Corner, Least Cost and Vogel's Approximation Method (VAM) to find the initial problem resolution followed by the Stepping Stone method and Modified Distribution (MODI) to determine the optimum solution. Before using the Transportation Method, X Indah Tea Factory spent a distribution cost was IDR. 69,900,000,- in March 2019, after using the transportation method, the distribution cost was IDR. 64,400,000,- so the company saves distribution costs of IDR. 5,500,000 every month. This method is recommended that factories located in Bojonggambir should distribute dry tea only to Singaparna, Bandung, Sumedang and Purwakarta. Whereas the factory located in Bantarkalong should distribute the tea to Subang, Sukabumi and fulfill some of the requests from Purwakarta in order to achieve optimum distribution costs.